CHARACTERISTIC OF TRADERS AND SANITATION CONDITIONS OF TRADITIONAL MARKET IN PALEMBANG - Amin, Maliha; Dinda Ayu Azizah Radi; Kamsul, Kamsul (Indonesia Epidemiological Journal, 2025)
Background: Poor sanitation conditions in the market can cause various diseases. Supervision of market sanitation needs to be carried out continuously by various parties as an effort to minimize the transmission of diseases and environmental health problems. The objective of the study was to analyze the market sanitation conditions and characteristics of traders in Palembang city markets. Methods: This study is an observational study with a cross-sectional design. This study was conducted in February-May 2024. The research sample was 54 traders and market conditions at Pasar 3-4 Ulu Palembang. Data were collected using questionnaires by means of observation. Results: The results of this study obtained that the sanitation conditions of Market 3-4 Ulu were in the category of not meeting requirements (59.0%), such as water for hygiene sanitation needs, toilets, and handwashing places. The characteristics of traders aged 51-56 who were still productive working 31 (57.4%) were that many were also female 36 (66.7%), working hours were ≥8 hours 14 (25.9%), and the lowest education was 38 (70.4%) traders. The level of knowledge of traders was low 21 (38.9%). Conclusion: The sanitation conditions of traditional markets in Palembang City were found to be substandard, and the majority of traders were women with low levels of knowledge regarding market sanitation.